Intercomparison of methods for determination of resonant frequency shift of a microstrip patch antenna loaded with Hevea rubber latex - Yahaya, Nor Zakiah; Abbas, Zulkifly; Mohd Ali, Borhanuddin; Ismail, Alif; Ansarudin, Farizah (Hindawi Publishing Corporation, 2014)
This paper presents an intercomparison between the finite element method, method of moment, and the variational method to determine the effect of moisture content on the resonant frequency shift of a microstrip patch loaded with wet material. The samples selected for this study were Hevea rubber latex with different percentages of moisture content from 35% to 85%. The results were compared with the measurement data in the frequency range between 1 GHz and 4 GHz. It was found that the finite element method is the most accurate among all the three computational techniques with 0.1 mean error when compared to the measured resonant frequency shift. A calibration equation was obtained to predict moisture content from the measured frequency shift with an accuracy of 2%.